Effect of photoperiod and temperature on bioproduct production from juvenile sporophytes of Macrocystis pyrifera - Purcell, Diane; Wheeler, Thomas T.; Hayes, Maria; Packer, Michael A. (Frontiers in Marine Science, 2024)
The giant kelp (Macrocystis pyrifera (Linnaeus) C. Agardh 1820) is a habitat-forming brown seaweed in temperate systems with an unexplored potential as a source of seaweed bioproducts. This study used M. pyrifera sporophytes sourced in Tasmania, Australia, to investigate the effect of photoperiod and temperature on growth rates and the nutritional characteristics of the resulting juvenile biomass. Four cultivation treatments combined growth temperatures of 12 °C, 15 °C, 18 °C with light:dark (L:D) of 12:12 and 16:8 (L:D) photoperiods, (12 °C – (12:12); 12 °C – (16:8); 15 °C – (12:12); 18 °C – (12:12) to investigate their effect on the number and size of sporophytes, biomass accumulation and nutritional composition. After 60 days of cultivation the 12 °C – (12:12) treatment had the greatest number of juvenile sporophytes, and the greatest biomass of 14 ± 1.3 g dry weight (DW). The lowest biomass of 1 g DW, was obtained from the 18 °C – (12:12) treatment. The protein content across all treatments ranged from 16-22.48% DW, with the 12 °C (12:12) treatment having largest range, then the 12°C (16:18) treatment was next with 18.48-22.48% DW, and the 15°C (12:12) treatment had the lowest protein range with 16.48-18% DW. These results are in the range of protein content previously reported for brown seaweeds of 5-20%. Total polysaccharide content ranged from 9.6-16.2% DW with the highest content of 16.2% DW obtained for the 15 °C – (12:12) treatment, and the lowest total polysaccharide content of 9.6% DW obtained for the 12 °C (16:18) treatment. After 66 days of cultivation, the highest yield of sulphated polysaccharides of 0.4% DW was obtained for the 12 °C (12:12) treatment. Total fatty acids were analysed, with the highest polyunsaturated fatty acid content of 60.4% detected in the 12 °C (12:12) treatment. This study demonstrates that temperature and photoperiod are factors impacting juvenile sporophyte growth, biomass accumulation and biochemical composition. The study showed the least stressed sporophytes produced the most potentially beneficial nutritional or bioactive profile.